Long-Term Optical Monitoring of Blazars - Gazeas, Kosmas (Galaxies, 2019)
Systematic monitoring of specific targets in the optical regime was historically applied on a very narrow sample of known variable stars. The discovery of blazars in the 20th century brought to the foreground the need for new global sky surveys, covering the entire sky and fainter sources. Full-sky surveys are conducted more easily from space observatories, while radio telescopes perform follow up observations from the ground. Blazars are detected in a wide range of energies, while they exhibit strong variability in various wavelengths from γ-rays and X-rays to the optical and radio domain. This results in a detailed classification, according to their emission properties in each region. The rapid variability in optical domain makes blazars interesting targets for optical sky surveys, offering a new opportunity to study their variability in the time domain. Digital sky surveys in optical and near-IR found a fertile ground with the aid of sensitive sensors. Only a few dedicated programs are focusing on blazar variability, a trend which evolved rapidly in the last decade. Modern techniques, in combination with dedicated sky survey programs lead towards a new era of long-term monitoring of blazars, aiming towards the search or variability on various time scales. In this work, an overview of blazar optical surveys and monitoring projects is given, addressing the major points of each one, and highlighting the constraints that the long-term study of blazars will bring through future international campaigns.